2020
DOI: 10.1111/ina.12668
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics of colloidal nanomaterial suspensions and aerosolized particulates from nano‐enabled consumer spray products

Abstract: Physicochemical properties between colloidal engineered nanomaterials (ENMs) and aerosols released from consumer spray products were characterized. A dynamic light scattering (DLS), transmission electron microscopy (TEM), and inductively coupled plasma mass spectrometer (ICP‐MS) were used to evaluate the suspended ENMs in the products. Direct‐reading instruments, TEM, and ICP‐MS were used to characterize the properties of aerosolized ENMs. The aerosolized organic compounds with ENMs were assumed to be vaporize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Based on the results of this study, VOCs must undergo a phase transition to a gaseous state when applied as liquid aerosols. Several studies using engineered nanoparticle (ENP) sprays (e.g., silver nanoparticles) observed that the spray nozzle types and size distribution of aerosols are important for estimating the inhalation exposure [ 29 , 30 , 31 , 32 , 33 ], although VOCs are expected to vaporize faster and achieve even distribution more easily than ENPs in spray products. The results of this study suggest that the estimation of inhalation exposure to VOCs should consider the spatial uncertainty, particularly regarding short-term exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study, VOCs must undergo a phase transition to a gaseous state when applied as liquid aerosols. Several studies using engineered nanoparticle (ENP) sprays (e.g., silver nanoparticles) observed that the spray nozzle types and size distribution of aerosols are important for estimating the inhalation exposure [ 29 , 30 , 31 , 32 , 33 ], although VOCs are expected to vaporize faster and achieve even distribution more easily than ENPs in spray products. The results of this study suggest that the estimation of inhalation exposure to VOCs should consider the spatial uncertainty, particularly regarding short-term exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing concern that the hazardous substances these products contain could adversely affect human health 1,3-6 . Several studies have analyzed the hazardous substances in various consumer spray products, such as detergents, coatings, diffusers, and disinfectants [7][8][9][10][11][12][13] . Building on these studies, further assessments of emission rates and consumer exposure to hazardous substances in the indoor environment associated with the use of certain products have been conducted [14][15][16][17][18][19][20] .Previous studies have analyzed volatile organic compounds (VOCs) in various household chemical products, but there is no internationally standardized sampling method available for aerosol spray products.…”
mentioning
confidence: 99%